Encouraging Women to Expand their Business Capabilities in Pangkalan Jati District Depok City, West Java - Yuliniar; khoirul aswar (JCOMMITS: Journal of Community Empowerment, Inovation, and sustainability, 2024)
As human resources, women essentially possess the capacity to engage in a variety of productive activities that yield outcomes and can support the family economy more generally in order to support the national economy. This is achieved through consistent and ongoing empowerment activities that enable women to become economically independent in the age of globalisation and information technology. The culinary industry is still stagnant and developing slowly after COVID, so efforts are required to boost company capacity through mentoring and training. The empowerment of women in the culinary industry—a field that is closely related to women's everyday lives—will be the activity that is conducted. It is hoped that by participating in this business capacity building activity, women will be able to engage in innovative and sustainable business ventures that not only support the family economy but also advance regional development in the area where the business is located